1996
DOI: 10.1159/000217312
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis And Clinical Characteristics Of Inherited Activated Protein C Resistance

Abstract: The diagnostic strategies and clinical characteristics of thrombophilia associated with heterozygous or homozygous factor V Leiden mutation have been determined according to the literature and to a personal study in 51 families. Factor V mutation was present in the 51 propositi and in 84 out of 125 family members (81 heterozygous, 3 homozygous). Venous thrombosis was observed in all the propositi, in 17 of the 84 family members with the mutation and in 6 of the 41 with a normal APC resistance test and no mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Several studies quickly followed that discovery and proved a positive association between FVL and VTE, showing that heterozygous carriers of the mutation are at higher risk of developing VTE by 10-fold while homozygous carriers have a much higher risk ratio reaching 140-fold (Dahlbäck et al, 1993;Zöller et al, 1994;Bertina et al, 1994;Hoagland et al, 1996;Dahlbäck, 1997;Faioni et al, 1997;Alderborn et al, 1997;Bontempo et al, 1997). Moreover, most homozygous cases were found to get at least one VTE event in their life time, and at an earlier time of their life (Samama et al, 1996;Florell & Rodgers, 1997). The identification of APC-R/FVL and its high risk value have exploded a massive rush in researches to study this new disease, its prevalence and its relationship with VTE in almost every part of the world.…”
Section: Activated Protein C Resistance (Apc-r) and Factor V Leiden Mmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies quickly followed that discovery and proved a positive association between FVL and VTE, showing that heterozygous carriers of the mutation are at higher risk of developing VTE by 10-fold while homozygous carriers have a much higher risk ratio reaching 140-fold (Dahlbäck et al, 1993;Zöller et al, 1994;Bertina et al, 1994;Hoagland et al, 1996;Dahlbäck, 1997;Faioni et al, 1997;Alderborn et al, 1997;Bontempo et al, 1997). Moreover, most homozygous cases were found to get at least one VTE event in their life time, and at an earlier time of their life (Samama et al, 1996;Florell & Rodgers, 1997). The identification of APC-R/FVL and its high risk value have exploded a massive rush in researches to study this new disease, its prevalence and its relationship with VTE in almost every part of the world.…”
Section: Activated Protein C Resistance (Apc-r) and Factor V Leiden Mmentioning
confidence: 97%
“…Only 10% of TFPI is present as a free active form in the blood while the majority is in combination with lipoproteins. Deficiency in TFPI may lead to a hypercoagulable state and hence VTE (Novotny et al, 1989;Novotny, 1994;Samama et al, 1996;Cella et al, 1997;Ehsan & Plumbley, 2002). TFPI decreased activity was noticed to contribute in developing thrombosis in women using oral contraceptives, and in patients with paroxysmal nocturnal haemoglobinuria (Maroney & Mast;2008).…”
Section: Tissue Factor Pathway Inhibitor (Tfpi) Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] It is present in a high number of Caucasians, 1,4,6,7,[10][11][12][13][14][15][16][17][18][19][20] but it is very rare in other ethnic groups. 7,17,[20][21][22][23][24][25] Few studies on Arabs showed that the prevalence of FVL was 0-27% in different Arabic countries, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] being as low as zero in countries like Saudi Arabia, 7,29,40 Oman 34 and Yemen, 27 whereas being relatively very high (27%) in Palestinians (Israeli Arabs).…”
Section: Delta Rnmentioning
confidence: 99%
“…FVL was reported to be highly present in populations of Caucasian origin living in Europe, United States and Australia, with a prevalence of 15-65% among VTE patients and 1-15% in the normal populations studied. 1,4,6,7,[10][11][12][13][14][15][16][17][18][19][20] On the other hand, FVL was almost absent in other populations such as Africans, South-East Asians, Chinese, Japanese, American Indians, Greenland Eskimos and Aboriginals of Australia. 7,17,[20][21][22][23][24][25] In Kuwait, VTE is quite common.…”
mentioning
confidence: 99%